Dynamic risk-based optimization on cryptocurrencies - Bayu Adi Nugroho (Journal of Capital Markets Studies (JCMS), 2021)
Purpose - It is crucial to find a better portfolio optimization strategy, considering the cryptocurrencies' asymmetric volatilities. Hence, this research aimed to present dynamic optimization on minimum variance (MVP), equal risk contribution (ERC) and most diversified portfolio (MDP). Design/methodology/approach - This study applied dynamic covariances from multivariate GARCH(1,1) with Student's-t-distribution. This research also constructed static optimization from the conventional MVP, ERC andMDPas comparison. Moreover, the optimization involved transaction cost and out-of-sample analysis from the rolling windows method. The sample consisted of ten significant cryptocurrencies. Findings - Dynamic optimization enhanced risk-adjusted return. Moreover, dynamic MDP and ERC could win the na exteuroive strategy (1/N) under various estimationwindows, and forecast lengths when the transaction cost ranging from 10 bps to 50 bps. The researcher also used another researcher's sample as a robustness test. Findings showed that dynamic optimization (MDP and ERC) outperformed the benchmark. Practical implications - Sophisticated investors may use the dynamic ERC and MDP to optimize cryptocurrencies portfolio. Originality/value - To the best of the author's knowledge, this is the first paper that studies the dynamic optimization on MVP, ERC and MDP using DCC and ADCC-GARCH with multivariate-t-distribution and rolling windows method.
Keywords: F30; G11; G15; 330; Cryptocurrencies; Minimum variance; Equal risk contribution; Most diversified portfolio; Multivariate GARCH